KERJASAMA ORANG TUA DAN GURU DALAM PENYELENGGARAAN PEMBELAJARAN ONLINE SEBAGAI UPAYA PENCEGAHAN VIRUS CORONA DI MI MUHAMMADIYAH PASIRMUNCANG - Yuni Kartini (STAI Sufyan Tsauri Majenang, 2020)
The purpose of this research is to describes about collaborative efforts of school and parents, forms of collaboration between parents and teachers, inhibiting factors, efforts to overcome barriers and parental involvement and also the role of teachers in the online learning process at MI Muhammadiyah Pasirmuncang. This research uses a qualitative approach with descriptive analysis type. The data collection techniques are interview, observation and documentation. The data analysis used consists data reduction, data presentation, and conclusion drawing. The data source are principle, teachers and parents of students at MI Muhammadiyah Pasirmuncang. The result of this research conducted at MI Muhammadiyah Pasirmuncang showing that online learning through collaboration and communication between parents and teachers is effective.